Efficacy of nutraceuticals (probiotics or prebiotics or synbiotics) in the prevention or treatment of COVID -19: a systematic review and meta-analysis - Anju Pradhan Sinha; Mahalaqua Nazli Khatib; Abhay Gaidhane; Shilpa Upadhyay; Mayur Wanjari; Syed Zahiruddin Quazi (Cogent Food & Agriculture)
Nutraceuticals have generated an interest among clinicians for their applicability in the prevention and treatment of many ailments. Literature suggests the possible role of nutraceuticals in COVID-19. However, substantial uncertainty related to their safety and efficacy still exists. The aim of this study is to assess the efficacy and safety of nutraceuticals in preventing or treating COVID-19. We searched electronic databases, registries, websites, and e-libraries of development agencies. We included randomized controlled trials (RCTs), quasi-experiments, pre-post studies, and other experimental study designs. We assessed the risk of bias (RoB) using the RoB2 tool for RCTs and the ROBINS-I tool for non-RCTs. We assessed the overall certainty of the evidence using GRADEpro GDT. The outcomes assessed were the number of COVID-19 cases, change in disease severity, days of hospitalization, deaths, and adverse events. We performed the last search on 13th December 2023. After screening 481 studies, our analysis of five revealed one study with ‘low risk’ and four studies with ‘some concerns’ regarding bias. Our findings indicated that nutraceuticals did not significantly reduce COVID-19 mortality; their effect on hospitalization duration was uncertain. Furthermore, our assessment found no substantial evidence of increased adverse effects with probiotic use (RR 0.11, 95% CI 0.01 to 1.89, P = 0.13). Importantly, none of the studies investigated nutraceuticals’ preventive effects or their role in mitigating COVID-19 severity. There is limited evidence available on the use of nutraceuticals (probiotics, prebiotics, or synbiotics) for the treatment and prevention of COVID-19. Conducting methodologically robust RCTs with large population samples is recommended.PROSPERO REGISTRATION ID CRD42021284923